(untitled) (Research, Society and Development, 2022)
The current society is marked is marked by the increase of mental illness making the data alarming, therefore, the article aims to present the importance of caring for the mental health of nursing professionals in relation to the care of patients with COVID-19. Elaborated from a review from an integrative literature review, search was carried out in a database with scielo, PAHO, WHO, pubmed and others, being withdrawn articles from 2001 to 2022. Listing the main disorders developed at that time, as well as related symptoms, A timeline was drawn that shows the rapid advance of the transmission of the virus that caused overcrowding in hospitals, work overload and, consequently, an increase in problems related to the mental health of these professionals. with this research it is expected to contribute to the care with health not only physical, but also mental is a subject approached with care and attention in the work institutions, in view of the exaggerated growth of workers with psychological disorders.